Do Physically Literate Adolescents Have Better Academic Performance?. Issue 4 (August 2019) - Gu, Xiangli; Zhang, Tao; Lun (Alan) Chu, Tsz; Zhang, Xiaoxia; Thomas Thomas, Katherine
This study examined the relationship between physical literacy (i.e., motor competence, physical activity, and health-related fitness) and academic performance (i.e., executive function, class attendance, and standardized test scores) among adolescents. Second, we investigated whether these relationships differ between boys and girls using a structural invariable test. Using a prospective research design, we recruited 330 adolescents (154 boys and 176 girls; M age = 12.52 years, SD = 0.86) in Texas and conducted correlational analyses, finding that physical literacy variables were significantly related to executive function (while the r s range was from −.16 to −.30, the high scores on the instrument we used, the Behavior Rating Inventory of Executive Function, indicate higher risks for executive dysfunction; p < .01) and positively associated with school attendance ( r s range from .19 to .34; p < .05). Structural equation models supported the significant direct and indirect effects of motor competence on executive function and school attendance for boys and girls through physical fitness (all three components) and school-based moderate-to-vigorous physical activity, respectively. The structural invarince test indicated noninvariant models (based on path coefficients) between girls and boys ( p < .01). Embracing psychomotor associations with physical literacy may be a promising way to elicit behavioral change in physical fitness and create a behavioral channel to academic success for adolescents.